Tapering and peaking for optimal performance - Mujika, Inigo (Human Kinetics, 2009)
Presents scientific data on tapering, its physiological and psychological effects and how these effects relate to athletic performance. Featuring various training models and experiential knowledge, this book allows readers to design optimal tapering programmes for each athlete.